Evaluation of Fitness and Accuracy of Milled and Three-Dimensionally Printed Inlays - Lim, Yoen Ah; Kim, Jeong Mi; Choi, Yoorina; Park, Sujung (European Journal of Dentistry, 2023)
Objective This article compares and evaluates the marginal and internal fitness and three-dimensional (3D) accuracy of class II inlays fabricated using Tescera (TS) resin, milling of hybrid and zirconia blocks, and 3D printing with NextDent C&B.Materials and Methods Fifty-two mesio-occlusal inlays were fabricated using conventional method with TS, milling of Lava Ultimate (LU), milling of Zolid Fx multilayer (ZR), and 3D printing (n = 13 each). The marginal and internal fitness were evaluated at six points in the mesio-distal section of a replica under a digital microscope (160× magnification), and the accuracy was evaluated using 3D software. Analyses were conducted using t-test, one-way analysis of variance (ANOVA) and two-way ANOVA, while Duncan's multiple range test was used for post hoc analyses (α = 0.05).Results The marginal and internal fitness of the 3D and ZR were significantly superior to that of the TS and LU. For LU, ZR, and 3D, a significant discrepancy between the marginal gap and internal gap was observed (p < 0.05). On evaluating accuracy, trueness was significantly higher in ZR than in TS and LU; precision was significantly higher in 3D and ZR than in TS and LU (p < 0.05).Conclusion The marginal and internal fitness and the accuracy of TS, ZR, and 3D were within the clinically acceptable range. The marginal and internal fitness and accuracy of 3D were better than those of TS and LU, which are commonly used in dentistry. There is immense potential for using 3D-printed inlays in routine clinical practice.
Keywords: 3D print; inlay; fitness; precision